Surgical treatment of perforated gastroduodenal peptic ulcers:comparison between open and laparoscopic approach - Trejo-Ávila, Mario E.; Solórzano-Vicuña, Danilo; Valenzuela-Salazar, Carlos; Muñoz-Gutiérrez, Rodrigo; Romero-Loera, Sujey; Moreno-Portillo, Mucio (International Surgery Journal, 2016)
Background: Laparotomy has long been the standard treatment of perforated peptic ulcers. Laparoscopy allows the confirmation of the diagnosis, better magnified visualization during the procedure and the identification of the position, site and size of the ulcer. The aim of this study is to compare the surgical outcomes of patients with perforated gastric or duodenal peptic ulcers treated either open or laparoscopic in our institution. Methods: We retrospectively reviewed records of patients with perforated peptic ulcers who underwent laparoscopic repair or open repair, from January 2013 to May 2016 in our hospital. We analyzed preoperative patient baseline parameters, and intraoperative and postoperative outcomes. Results: Repair of perforated peptic ulcers was performed in 27 patients, using laparoscopic surgery for 14 patients and open surgery for 13 patients. The comparison between the two groups revealed statistically similar results regarding age, gender, BMI and ASA score. Laparoscopic repair was associated with less estimated blood loss (20 vs. 121.5 mL, p=0.025), less duration of nasogastric decompression (1.2 vs. 3.4 days, p=0.000), faster return to diet (2.5 vs. 4 days, p=0.0001) and shorter hospital length of stay (5.5 vs. 7 days, p=0.019). There were no significant differences between the two procedures with regard to operative time (103.9 vs. 101.2 min), use of abdominal drains (71.4% vs. 76.9%) and in-hospital complications (7.1% vs. 15.4%). Conclusions: Laparoscopic repair of gastroduodenal perforations provides a safe and feasible alternative treatment to perforated gastroduodenal peptic ulcers. Results in our study are in concordance with results published globally.